Lessons Learned from Developing a Trauma Consultation Protocol for Juvenile and Family Courts. (September 2016) - Marsh, Shawn C.; Summers, Alicia; DeVault, Alicia; Guillermo Villalobos, J.
Abstract: Juvenile and family courts hold a unique position among the many stakeholders that comprise a healing community for persons experiencing adversity or trauma. Specifically, judges and other court leaders can promote the implementation of screening for trauma, the alignment of appropriate and effective treatment for trauma when indicated, and the accountability of systems for coordination and support of such services. To that end, the National Council of Juvenile and Family Court Judges undertook a field‐based project — consisting of multiple semi‐structured court surveys — to elucidate the key features of a trauma‐informed court and how to assist courts in becoming more trauma‐responsive for both consumers and staff. With the assistance of courts in 11 pilot sites across the nation, the project has led to the development of a protocol called trauma consultation or trauma audit, which is outlined here. Our work in developing the consultation protocol highlighted the need to better understand (1) the prevalence and impact of secondary traumatic stress in court staff, (2) the potential for environment to contribute to traumatic stress reactions, and (3) the importance of consistent trauma screenings and subsequent use of findings. Practical suggestions for courts to become more trauma‐informed are also provided.